Apolipoprotein E epsilon4 and testosterone interact in the risk of Alzheimer's disease in men. - Hogervorst, E; Lehmann, D; Warden, DR; McBroom, J; Smith, A (2002)
OBJECTIVES: To assess the association between testosterone levels and APOEepsilon4 in cases with AD and controls. METHOD: We included 61 men with definite or probable Alzheimer's disease (AD) and 55 elderly male controls from the Oxford Project to Investigate Memory and Ageing (OPTIMA). Testosterone was measured using a competitive enzyme immunoassay (Bayer). RESULTS: We found that both low serum testosterone and the interaction between testosterone and APOEepsilon4 were associated with AD. Furthermore, testosterone levels were lower in APOEepsilon4-positive controls (mean: 11.3 nmol/L) than in controls without the allele (19.1 nmol/L). CONCLUSIONS: Low testosterone is potentially a modifiable risk factor, which may prove relevant to APOEepsilon4 carriers who are at risk of AD.